Comparative effectiveness and safety of oral anticoagulants for atrial fibrillation in real-world practice: a population-based cohort study protocol. Issue 11 (24th November 2016) - Holbrook, Anne; Dormuth, Colin; Morrow, Richard; Lee, Agnes; Troyan, Sue; Li, Guowei; Pullenyegum, Eleanor
Abstract : Introduction: Anticoagulants are arguably the most important drug family of all, based on the frequency and duration of their use, and the clinical importance and frequency of benefits and harms. Several direct acting oral anticoagulants (DOACs) have recently joined warfarin for the treatment of atrial fibrillation, with a resultant significant expansion in use of oral anticoagulants (OACs). Our objectives are to compare safety and effectiveness of DOACs versus warfarin in a full population where anticoagulation management is good and to identify which types of patients do better with DOACs versus warfarin and vice versa. Methods and analysis: This is a retrospective cohort study of all adults living in British Columbia who have a diagnosis of atrial fibrillation in hospital or medical service data, and a first prescription for an OAC. Coprimary outcomes are ischaemic stroke and systemic embolism (benefit) and major bleeding (harm). Secondary outcomes include net clinical benefit (composite of stroke, systemic embolism, major bleeds, myocardial infarction, pulmonary embolism and death), drug discontinuation and individual composite item occurrence. We will estimate the effects of treatment in a 2-year follow-up period, using time-to-event models with propensity score adjustment to control confounding. Secondary analyses will examine 'as treated' outcomes. Ethics and dissemination: The protocol, data creation plan, privacy impact statement and data sharing agreements have been approved. Dissemination is planned via conferences and publications as well as directly to drug policy leaders. Information on the overall comparative effectiveness and safety of DOACs versus warfarin in a country with high quality anticoagulation management, as well as for vulnerable subgroups, will be an important addition to the literature.